Coagulase gene polymorphism, enterotoxigenecity, biofilm production, and antibiotic resistance in Staphylococcus aureus isolated from bovine raw milk in North West India - Vishnu Sharma; Sanjita Sharma; Dinesh Kumar Dahiya; Aarif Khan; Manisha Mathur; Aayushi Sharma (Annals of Clinical Microbiology and Antimicrobials, 2017)
Abstract Background Staphylococcus aureus is the predominant bacterium responsible for various diseases in animals and humans. Preventive strategies could be better implemented by understanding the prevalence, genetic patterns, and the presence of enterotoxin and biofilm-producing genes along with the antibiotic susceptibility of this organism. This study was conducted in Rajasthan, the northwestern state of India, holding the largest population of cattle that makes it the second largest milk producer in India and no such prior information is available on these aspects. Methods A total of 368 individual quarter bovine raw milk samples were collected from 13 districts of Rajasthan, and screened for the presence of S. aureus. Microbiological and molecular approaches were followed for bacterial identification. Genetic diversity was determined by polymerase chain reaction-restriction fragment length polymorphism (PCR–RFLP) of coagulase gene (coa), whereas enterotoxin and biofilm-producing genes were studied by PCR analysis. Antibiotic strips were employed to study the antibiotic resistance among strains. Results In all, 73 S. aureus strains were obtained from 368 bovine raw milk samples out of that only 30 showed the presence of coa. Nine types of coa patterns ranging from 730 to 1130 bp were observed among these isolates. PCR–RFLP of coa distinguished the isolates into 15 genotypic patterns, of which patterns I, IV, V, and VI were predominant. Of the isolates, 30% were positive for sec, 10% for sea, and 3.3% for seb; these genes are responsible for enterotoxin production, whereas all isolates were found positive for icaAD and eno. The prevalence rates of other biofilm-producing genes fnbA, clfB, ebpS, sasG, fnbB, sasC, cna, bap, fib and, bbp were 97, 93, 90, 80, 80, 77, 53, 27, 10, and 6.6%, respectively. Twenty-seven (90%) strains were multidrug resistant, of which 15 were methicillin resistant. Maximum sensitivity was reported for kanamycin and it could be considered as a drug of choice for controlling S. aureus mediated cattle infections in the studied regions. Conclusions Overall, these strains could cause several diseases to humans, insisting the need for developing a stricter hygiene program for improving milking practices and animal health.